How Influencer Marketing Shapes Tourist Citizenship Behavior for Sustainable Tourism Destinations? The Mediating Role of Brand Attitude - Wulyatiningsih, Toetik; Rantung, Nancy Margaretha; Mandagi, Deske W. (International Review of Management and Marketing, 2025)
This study investigates how influencer marketing shapes tourist citizenship behavior (TCB) in sustainable tourism through the mediating role of brand attitude. Building on social exchange theory and consumer–brand relationship literature, the study addresses a gap in understanding the mechanisms by which digital influence extends beyond purchase intentions to pro-social tourist behaviors. Survey data from 250 visitors to sustainable destinations in North Sulawesi, Indonesia, were analyzed using structural equation modeling (SmartPLS). Results show that influencer marketing significantly enhances brand attitude, which directly fosters TCB dimensions such as advocacy, feedback, helping, and tolerance, and mediates the relationship between influencer marketing and TCB. These findings highlight the strategic role of brand attitude in translating digital influence into sustainable, community-oriented tourist practices. Theoretically, the study advances knowledge by integrating influencer marketing with behavioral outcomes in sustainable tourism, moving beyond traditional attitudinal or intention-based measures. Practically, it offers insights for policymakers and destination marketers on designing authentic and ethical influencer campaigns that strengthen sustainable brand–consumer relationships. Limitations concerning geographic scope and cross-sectional design suggest directions for broader and longitudinal investigations.